2019
DOI: 10.1155/2019/2924961
|View full text |Cite
|
Sign up to set email alerts
|

CO2-Philic [EMIM][Tf2N] Modified Silica in Mixed Matrix Membrane for High Performance CO2/CH4 Separation

Abstract: Separation of carbon dioxide (CO2) from methane (CH4) using polymeric membranes is limited by trade-off between permeability and selectivity as depicted in Robeson curve. To overcome this challenge, this study develops membranes by incorporating silica particles (Si) modified with [EMIM][Tf2N] ionic liquid (IL) at different IL:Si ratio to achieve desirable membrane properties and gas separation performance. Results show that the IL:Si particle has been successfully prepared, indicated by the presence of fluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The evaporated moisture from the surface would be carried out of the drier by suitable air speed. Furthermore, heated air conveyed the energy utilised to evaporate moisture at the coffee beans surface [13][14][15].…”
Section: Data Of the Simulationmentioning
confidence: 99%
“…The evaporated moisture from the surface would be carried out of the drier by suitable air speed. Furthermore, heated air conveyed the energy utilised to evaporate moisture at the coffee beans surface [13][14][15].…”
Section: Data Of the Simulationmentioning
confidence: 99%
“…The results showed that the CO 2 solubility property of anion had influenced the CO 2 permeability of the IL‐MMM. A similar impregnation method was also applied by other researchers in the modification of the inorganic fillers with IL before MMM fabrication 206,207 . Besides the simple impregnation method, Ilyas et al 208 used another modification approach to introduce the IL on the zeolite surface.…”
Section: Il‐based MMMmentioning
confidence: 99%
“…It has been identified that before reaching the plasticization pressure, the gas sorption mechanism follows the dual sorption model, which is typical for the glassy polymer. The Langmuir sites become saturated in the low‐pressure region, leading to permeability reduction 207 . Meanwhile, beyond the plasticization pressure, the gas transport mechanism is dominated by plasticization behavior 41 …”
Section: Il‐based MMMmentioning
confidence: 99%
“…Inorganic particles that are non-porous, for instance, silica, are used in membranes of nanocomposite structures [53,86]. Previous works stated that the additional void located at the interface between silica agglomerates and the polymers has the probability to induce permeability enhancement [114,125,126]. Sadeghi et al [127] studied CH4 and CO2 properties of transport through composite membrane made of silica and polybenzimidazole (PBI).…”
Section: Hybrid and Composite Membranesmentioning
confidence: 99%